A scoping review of interprofessional collaborative practice and education using the lens of the Triple Aim. Issue 5 (September 2014) - Brandt, Barbara; Lutfiyya, May Nawal; King, Jean A.; Chioreso, Catherine
Abstract The Triple Aim unequivocally connects interprofessional healthcare teams to the provision of better healthcare services that would eventually lead to improved health outcomes. This review of the interprofessional education (IPE) and collaborative practice empirical literature from 2008 to 2013 focused on the impact of this area of inquiry on the outcomes identified in the Triple Aim. The preferred reporting items for systematic reviews and meta-analyses methodology were employed including: a clearly formulated question, clear inclusion criteria to identify relevant studies based on the question, an appraisal of the studies or a subset of the studies, a summary of the evidence using an explicit methodology and an interpretation of the findings of the review. The initial search yielded 1176 published manuscripts that were reduced to 496 when the inclusion criteria were applied to refine the selection of published manuscripts. Despite a four-decade history of inquiry into IPE and/or collaborative practice, scholars have not yet demonstrated the impact of IPE and/or collaborative practice on simultaneously improving population health, reducing healthcare costs or improving the quality of delivered care and patients' experiences of care received. We propose moving this area of inquiry beyond theoretical assumptions to systematic research that will strengthen the evidence base for the effectiveness of IPE and collaborative practice within the context of the evolving imperative of the Triple Aim.